CHARACTERISTICS OF FROZEN FISH RESULTS FROM THE CATCH STOCKING ON A CONTAINING VESSEL KM. SEA OF BERLIANS-99 AT PPP MAYANGAN - Mbete, Saverinus; Sitanggang, Wanri; Alamsah, Safingi; Afrisal, Muhammad; Pramudya, Herning; Ismail, Masrurah; Beshari, Hanasajida Edelweiss; Nugilestari, Annie Valentina; bonoventure, Krisanto; Usfintit, Junianus (Jurnal Perikanan Unram, 2025)
A fish collection vessel is a vessel specifically used to transport fish including the process of loading, holding, storing, cooling, and preserving fish on board. This research was conducted at the Mayangan Coastal Fisheries Port (PPP) with the aim of determining the characteristics of the types of fish catches collected at KM. Lautan Berlian-99 which were landed at PPP Mayangan. This research was conducted from September to November 2024 at PPP Mayangan using a qualitative method where data collection in this study was collected through the observation method, namely by directly observing the landing of fish at PPP Mayangan. The identification results showed ten types of fish that were successfully caught by fishermen from various fishing gear including purse seines, bottom longlines and drift nets. The fish were then put into the hold of the collection vessel by the transhipment process to be taken to the port. The measurements to be used are standard length measurements with units of cm. The measurements carried out include total length, half body length, tail length, eye height, body width, head width, and eye width.